Neonatal Arrhythmias: Atrial Flutter - M.O. Gonchar; H.S. Senatorova; A.D. Boichenko; A.F. Shipko; О.О. Riha; I.Yu. Kondratova; O.I. Strashok; A.V. Senatorova; Т.О. Теslenко; N.V. Gubar (Zaslavsky O.Yu., 2014)
The paper presents the current data on the diagnosis of neonatal arrhythmias, covers the prevalence, mechanisms of formation, diagnosis and treatment of one type of cardiac arrhythmias - atrial flutter. Clinical observation in terms of the diagnosis and treatment of atrial flutter in a newborn in the early neonatal period is given.